Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.178
|View full text |Cite
|
Sign up to set email alerts
|

Tight Competitive Ratios of Classic Matching Algorithms in the Fully Online Model

Abstract: Huang et al. (STOC 2018) introduced the fully online matching problem, a generalization of the classic online bipartite matching problem in that it allows all vertices to arrive online and considers general graphs. They showed that the ranking algorithm by Karp et al. (STOC 1990) is strictly better than 0.5-competitive and the problem is strictly harder than the online bipartite matching problem in that no algorithms can be (1 − 1/e)-competitive.This paper pins down two tight competitive ratios of classic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 9 publications
0
51
0
Order By: Relevance
“…We note that any α-competitive online matching under general vertex arrivals is α-competitive in the less restrictive model of Huang et al As observed by Huang et al, for their model an optimal approach might as well be greedy; i.e., an unmatched vertex v should always be matched at its departure time if possible. In particular, Huang et al [15,16], showed that the ranking algorithm of Karp et al is optimal in this model, giving a competitive ratio of ≈ 0.567. For general vertex arrivals, however, ranking (and indeed any maximal matching algorithm) is no better than 1 /2 competitive, as is readily shown by a path on three edges with the internal vertices arriving first.…”
Section: Prior Work and Our Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…We note that any α-competitive online matching under general vertex arrivals is α-competitive in the less restrictive model of Huang et al As observed by Huang et al, for their model an optimal approach might as well be greedy; i.e., an unmatched vertex v should always be matched at its departure time if possible. In particular, Huang et al [15,16], showed that the ranking algorithm of Karp et al is optimal in this model, giving a competitive ratio of ≈ 0.567. For general vertex arrivals, however, ranking (and indeed any maximal matching algorithm) is no better than 1 /2 competitive, as is readily shown by a path on three edges with the internal vertices arriving first.…”
Section: Prior Work and Our Resultsmentioning
confidence: 92%
“…On the hardness front, the problem is known to be strictly harder than the one-sided vertex arrival model of Karp et al [18], which admits a competitive ratio of 1 − 1 /e ≈ 0.632. In particular, Epstein et al [10] gave an upper bound of 1 1+ln 2 ≈ 0.591 for this problem, recently improved by Huang et al [16] to 2− √ 2 ≈ 0.585. (Both bounds apply even to online algorithms with preemption; i.e., allowing edges to be removed from the matching in favor of a newly-arrived edge.)…”
Section: Prior Work and Our Resultsmentioning
confidence: 94%
See 3 more Smart Citations